In Silico Selection And Validation Of Dna Aptamer Against Progesterone Receptor Dna Binding Domain - Tholasi Nadhan, Navien (2022)
Progesterone receptor plays an important role in the progression of breast cancer. Currently, antibody-based Immunohistochemistry is used in pathological assessment of PR levels for the detection of breast cancer. The shortcomings associated with antibodies pave the path to use aptamers as the alternatives. Aptamers are single-stranded DNA or RNA oligonucleotides generated by SELEX that are capable of binding to their cognate target molecules with high affinity and specificity based on their unique structural folding capacity.The tediousness and rigor associated with certain steps of the conventional SELEX intensify the efforts to select DNA aptamers using in silico-docking approach. That said, we report an in silico selection and validation of DNA aptamer to the progesterone receptor DNA binding domain (PR DBD) using ssDNA sequences derived from human progesterone response elements (PREs).Firstly, a library of sixty-four different nearnative ssDNA analogs of the corresponding PRE sequences was designed and subjected to secondary and tertiary structural determination. After that, docking between the ssDNA tertiary structures with the PR DBD was carried out using PatchDock. The sequence with the highest docking score was chosen as the aptamer candidate and further validated by in vitro direct ELASA.Among the candidates, we selected the ssDNA sequence (PRDBDapt17; 5′- AGAACAGCGTGTTCT -3′), which showed the highest docking scores of 11334 as a promising PR DBD binding aptamer. In addition, the PRDBDapt17 detected recombinant PR DBD in direct ELASA with a limit of detection of 3.91 nM. The dissociation constant was estimated at 366.6 nM. Therefore, PRDBDapt17 is a potential aptamer that can be used in the diagnosis of breast cancer.